Moments in the knee and hip during descent and ascent of squats - Gülay, T.; List, R.; Lorenzetti, S. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this study was to compare the moments in the knee and hip during the acceleration phases, namely the descent and the ascent phase of squats. 20 subjects executed barbell squats with zero, 25 %, and 50 % body weight (BW) extra load. Based on motion capture and force data, an inverse dynamic calculation of the load condition of knee and hip was performed. The free chosen time for one repetition was less than 2 s. According to Newton's second law, it is expected that during the acceleration phases of the body and the extra load, the load conditions are higher. The experimental data shows only shows small differences in the range of a few percent during the acceleration and deceleration phases of the squat. Therefore, the main part of the loading during squatting is based on the body weight and the barbell and not due to the acceleration of the mass.